Effect of feeding total mixed ration blocks on productive performance of crossbred dairy cattle - Sahib, Lasna; S, Pramod; B, Bibin Becha; R, Thirupathy Venkatachalapathy (Indian Journal of Dairy Science, 2020)
A feeding trial of four weeks was conducted using forty crossbred dairy cattle reared under intensive system. The animals were divided into 2 groups, based on milk yield, parity and stage of lactation and fed either a commercially available total mixed ration (TMR) blocks or conventionally available compounded cattle feed (in form of pellet) and green grass separately at different times of the day. The results indicated that the total daily milk yield was significantly lower (p